1997
DOI: 10.1200/jco.1997.15.2.653
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pegylated-liposomal doxorubicin in the treatment of AIDS-related Kaposi's sarcoma after failure of standard chemotherapy.

Abstract: Pegylated-liposomal doxorubicin offers a new alternative for treatment of patients who have experienced failure of standard chemotherapy for AIDS-KS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(74 citation statements)
references
References 10 publications
1
72
0
1
Order By: Relevance
“…13 PLD has activity in soft tissue sarcomas in general, 26 -28 and is highly active in KS. [17][18][19]25,33 Both KS and angiosarcoma are tumors of endothelial cells and may, therefore, share some biologic properties. We treated six patients with angiosarcomas with PLD, either as first-line therapy or in patients who experienced PD while receiving paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 PLD has activity in soft tissue sarcomas in general, 26 -28 and is highly active in KS. [17][18][19]25,33 Both KS and angiosarcoma are tumors of endothelial cells and may, therefore, share some biologic properties. We treated six patients with angiosarcomas with PLD, either as first-line therapy or in patients who experienced PD while receiving paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…14 -16 Pegylated-liposomal doxorubicin (PLD) is highly effective and has only minor toxicity in patients with KS, a tumor composed primarily of abnormal endothelial cells. [17][18][19] PLD is a formulation in which doxorubicin is contained in liposomes that are coated with methoxypoly-(ethylene glycol). The methoxypoly-(ethylene glycol) confers a decreased uptake by the reticuloendothelial system, a long half-life in blood (approximately 50 -60 hours), and a different toxicity from nonpegylated liposomes.…”
mentioning
confidence: 99%
“…Recent successes in this area of clinical research include the efficacy of liposomal doxorubicin in AIDS-related Kaposi's sarcoma and patients with refractory ovarian cancer (Muggia et al, 1997;Northfelt et al, 1997). Although the precise mechanisms by which liposomes selectively enter tumours and release drug are not completely understood, their successful application with doxorubicin has led to a resurgence of interest in this area.…”
Section: Discussionmentioning
confidence: 99%
“…ABV patients experienced significantly more alopecia and neuropathy, while liposomal daunorubicin patients had significantly more grade 4 neutropenia. A second study gave liposomal doxorubicin to 53 patients with AIDSrelated KS who had progressed through or were intolerant to combination therapy [90]. The study demonstrated a 36% PR rate and a median duration of response Ͼ4 months, helping to establish liposomal doxorubicin as a reasonable second-line drug.…”
Section: Treatmentmentioning
confidence: 99%